2003
DOI: 10.1200/jco.2003.12.097
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Evaluation of Temozolomide and 13-cis-Retinoic Acid for the Treatment of Recurrent and Progressive Malignant Glioma: A North American Brain Tumor Consortium Study

Abstract: P h a s e I I E v a l u a t i o n o f T e m o z o l o m i d e a n d 1 3 -c i s -R e t i n o i c A c i d f o r t h e T r e a t m e n t o f R e c u r r e n t a n d P r o g r e s s i v e M a l i g n a n t G l i o m a : A N o r t h A m e r i c a n B r a i n T u m o r C o n s o r t i u m S t u d yMedian overall PFS was 19 weeks (95% CI, 16 to 27 weeks), and median overall survival (OS) was 47 weeks (95% CI, 36 to 58 weeks). OS was 46% (95% CI, 36% to 57%) at 52 weeks and 21% (95% CI, 13% to 31%) at 104 weeks. Of 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(78 citation statements)
references
References 22 publications
0
76
0
2
Order By: Relevance
“…The frequent administration of certain cytotoxic agents at low doses, known as 'metronomic chemotherapy', was more effective in targeting tumor endothelium than large single bolus doses followed by treatment-free period (2,3,9,20). The current studies demonstrated efficacy as salvage therapy in the treatment of patients with breast cancer and hormone-refractory prostate cancer (4,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent administration of certain cytotoxic agents at low doses, known as 'metronomic chemotherapy', was more effective in targeting tumor endothelium than large single bolus doses followed by treatment-free period (2,3,9,20). The current studies demonstrated efficacy as salvage therapy in the treatment of patients with breast cancer and hormone-refractory prostate cancer (4,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is little evidence of benefit of chemotherapy after tumor recurrence or progression. Since the majority of them are no longer candidates for further irradiation or surgical intervention, considerable efforts have been recently focused in the investigation of new chemotherapeutic agents and treatment schedules for recurrent glioblastoma (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…As a single agent, cisretinoic acid has shown modest benefits in maintaining remission in malignant glioma [18][19][20] . Combination therapy with temozolomide and cis-retinoic acid at recurrence has shown considerable promise, yielding a 6-month progression-free survival (pfs-6) of 43% in a large phase ii study from the North American Brain Tumor Consortium 21 . However, that study antedated the use of temozolomide in chemoradiation strategies for newly diagnosed patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the past years results, of several novel combinations of alkylating agents with drugs with a different mode of action investigated in recurrent GBM have been published: cisplatin and TMZ, 33 marimastat and TMZ, 34 cisretinoic acid and TMZ, 35 thalidomide and carmustine 36 ( Table 3). Each of these combinations report high response rates and favourable percentages of patients free from progression at six months.…”
Section: Temozolomide In Combination With Other Cytotoxic Agentsmentioning
confidence: 99%